Exploring men’s health in medium and high complexity care in Brazil: A deductive thematic analysis of social determinants - Márcio Soares de Almeida; Bruna Rafaela Carneiro; Albert Ramon Oliveira Santos; Claudia Geovana da Silva Pires; Fransley Lima Santos; Alvaro Francisco Lopes de Sousa; Anderson Reis de Sousa; Álvaro Pereira; Layze Braz de Oliveira; Liliane Moretti Carneiro; Isabel Amélia Costa Mendes (Belitung Raya Foundation, Indonesia, 2024)
Background: Men’s health is influenced by a complex interplay of social, economic, and cultural determinants. Understanding how these aspects affect the health of adult cisgender men in medium and high-complexity healthcare settings is essential for improving healthcare services and promoting better health outcomes. Objective: This study aimed to analyze the health status of adult cisgender men in medium and high-complexity healthcare settings based on social determinants and conditioners. Methods: This study employed a qualitative design involving 45 adult cisgender men receiving care in medium/high complexity services in Bahia, Brazil. Semi-structured interviews were conducted from July 2019 to February 2020, and data were interpreted based on Dahlgren and Whitehead’s Model of Social Determinants of Health using deductive thematic analysis. Results: Proximal determinants included biological aspects, preventive behaviors, lifestyle/social life, and aging processes. Intermediate factors included work conditions, access/utilization of healthcare services/medications, and psychosocial factors. Macro determinants involved income distribution, power dynamics, resource allocation, health inequalities/iniquities, morbidity, culture, political decisions, environmental factors, and structural elements. Conclusion: The health status of men in medium/high complexity care was profoundly influenced by structural social determinants. These determinants impacted healthcare attention, service organization, cultural influences, the reproduction of hegemonic masculinity patterns, lifestyle, social support, and socioeconomic conditions necessary to realize the right to health. Nursing practices should conduct comprehensive assessments that extend beyond physical health indicators.